Tradução, adaptação transcultural e análise das propriedades de medida do Measure of Intermittent and Constant Osteoarthritis Pain (ICOAP) quadril para o português do Brasil em indivíduos com osteoartrite do quadril - Silva, Aron Charles Barbosa da (2022)
Objective: To perform the translation, cross-cultural adaptation, and validation of the Intermittent and Constant Osteoarthritis Pain (ICOAP) hip in patients with hip osteoarthritis into Brazil Portuguese. Materials and Methods: The process of translation and cross-cultural adaptation of the ICOAP hip into Brazil Portuguese followed international criteria, and the following stages were performed: translation, synthesis of the translations, back translation, analysis by an expert committee, testing of the pre-final version and definition of the final version. The study included individuals aged 40 or over, of both genders, with a medical diagnosis of hip osteoarthritis, complaining of pain and/or altered function in the lower limb(s) for 12 weeks or longer, and able to read and understand Portuguese. The psychometric properties evaluated were: structural validity through factor analysis (exploratory and confirmatory); test-retest reliability through the intraclass correlation coefficient (ICC); internal consistency through Cronbach's alpha; construct validity through the correlations between ICOAP and Numerical Pain Scale (NDS), Hip Disfunction and Osteoarthritis Outcome Score (HOOS), Medical Outcome Study 36 - Item Short-Form Health Survey (SF-36). Results: Fifty patients diagnosed with hip osteoarthritis were included for validity analyses, and a subsample of 50 patients was used for test-retest reliability. For structural validity, the original structure of the Portuguese hip ICOAP showed all adequate fit indices: chi-square/GL = 1.05; CFI = 1.00; TLI = 1.00; RMSEA (90% CI) = 0.024 (0.000 to 0.073); SRMR = 0.031. In the reliability analysis, it presents excellent values referring to test-retest reliability and internal consistency, with ICC value = 0.99 and Cronbach's alpha = 0.997 for the constant pain domain. And ICC = 0.99 and Cronbach's alpha = 0.996 for the intermittent pain domain. For the total score, adequate reliability and internal consistency were observed, with values of the intraclass correlation coefficient (ICC) ≥ 0.99, standard error of measurement (SEM) ≤ 8.60%, and Cronbach's alpha ≥ 0.997. Regarding construct validity, it was observed for the item constant pain and correlations greater than 0.50 between the ICOAP hip and HOOS, SF-36, and the NDT. Conclusion: The Brazilian version of the ICOAP hip with two domains and 11 items presents acceptable psychometric properties, supporting its use in patients with hip osteoarthritis.